Blackboard System and Students’ Academic Performance: An Experimental Study in The Philippines - Jomarie V. Baron (Journal of Social, Humanity, and Education, 2023)
Purpose: The main purpose of this study is to determine the Blackboard System's effectiveness on students' academic performance in Araling Panlipunan. Research methodology: The study employed a quasi-experimental pre-test and post-test non-equivalent group design and was entirely quantitative. Seventy (70) Ligaya High School students in Grade 7 who were divided into the control and experimental groups made up the study's subjects. Both groups received instruction on related subjects throughout the first quarter of the Araling Panlipunan grading period. The t-test for dependent and independent samples was the statistical tool employed to evaluate the hypothesis. Results: Results indicate that using the Blackboard System to teach Araling Panlipunan is a more effective approach than using the traditional lecture technique. Further, it has a significant impact on students and learning processes. Teachers also gained great benefits in using this system since it provided them an easy way of tracking student progress reducing a lot of paperwork load. Limitations: This study was limited to only Grade 7 Araling Panlipunan learners in the school year 2019-2020. The duration of the experiment was only focused on the First Quarter grading period. Contribution: One of the key goals of the study is to raise the standard of education by using new technological trends, which will assist them to advance their skills and competencies in technology. Teachers will also benefit from the study to help them improve their craft with the use of effective pedagogy with ICT to cope with the changing world.